Beneficial Immune Regulation by Biological Response Modifier Glucans in COVID-19 and Their Envisaged Potentials in the Management of Sepsis - Preethy, Senthilkumar; Raghavan, Kadalraja; Dedeepiya, Vidyasagar Devaprasad; Surya Prakash, Vaddi; Ikewaki, Nobunao; Ikeue, Yasunori; Nagataki, Mitsuru; Iwasaki, Masaru; Senthilkumar, Rajappa; Abraham, Samuel J. K. (Frontiers in Immunology, 2022)
Sepsis is a life-threatening condition caused by an abnormal immune response induced by infection with no approved or specific therapeutic options. We present our perspectives for therapeutic management of sepsis through a four-way approach: (1) infection control through immune enhancement; (2) immune-suppression during the initial hyper-inflammatory phase; (3) balanced immune-modulation to counter the later immune-paralysis phase, and (4) advantageous effects on metabolic and coagulation parameters throughout. COVID-19 is a virus-triggered, accelerated sepsis-like reaction, which is associated with the rapid progress of an inflammatory cascade involving a cytokine storm and multi-organ failure. Here, we discuss the potential of the biological response modifiers, β-glucans (BRMGs), in the management of sepsis based on their beneficial effects in inflammatory-immune events in COVID-19 clinical studies. In COVID-19 patients, apart from metabolic regulation, BRMG glucan, derived from a black yeast Aureobasidium pullulans strain AFO-202, has been reported to stimulate immune responses. BRMG produced by another strain (N-163) of A. pullulans, has been implicated in beneficial regulation of inflammatory markers and immunity, namely IL-6, C-reactive protein (CRP), D-Dimer, Ferritin, neutrophil to lymphocyte ratio (NLR), lymphocyte to C-reactive protein ratio (LCR), leucocyte to C-reactive protein ratio (LeCR), and Leukocyte to IL-6 ratio (LeIR). Agents such as these β-glucans, which are safe as they have been widely consumed by humans for decades, have potential as adjuncts for the prevention and management of sepsis as they exert their beneficial effects across the spectrum of processes and factors involved in sepsis pathology, including, but not limited to metabolism, infection, inflammation, immune modulation, immune enhancement, and gut microbiota.